Pengaruh Customer Experience dan Brand Trust TerhadapCustomer Loyalty pada Pelanggan Jasa PT Kai Logistik Kota Malang - Nurul Kholifah; Achmad Zaini (Indo Publishing, 2026)
The increasingly intense competition in the logistics industry requires PT KAI Logistik to rely not only on delivery speed, but also on building strong customer experience and brand trust to maintain customer loyalty, while research on customer experience and brand trust has so far been largely limited to the beauty sector and online shopping platforms, leaving the logistics service sector underexplored. This study aimed to determine and analyze the effect of customer experience and brand trust on customer loyalty among customers of PT KAI Logistik Malang, both partially and simultaneously. The study used a quantitative method with 100 respondents determined through the Cochran formula and purposive sampling technique, namely customers aged at least 17 years who had used PT KAI Logistik Malang's services more than 3 times. The data were collected through a 1-5 Likert scale questionnaire distributed both online and offline, then analyzed using multiple linear regression with the assistance of IBM SPSS Statistics 27. The results showed that customer experience and brand trust, both partially and simultaneously, have a positive and significant effect on customer loyalty, with an Adjusted R Square value of 0.799 indicates that 79.9% of the variation in Customer Loyalty can be explained by Customer Experience and Brand Trust, while the remaining 20.1% is influenced by other variables not examined in this study. Brand trust was found to be the most dominant variable compared to customer experience. It can be concluded that positive customer experience and strong brand trust are important factors in shaping customer loyalty in the logistics service sector, so that PT KAI Logistik needs to continuously maintain service quality and build customer trust in order to sustain loyalty amid industry competition.